Low-cost spherical Al-N-based powder with adjustable heat conductivity coefficient and preparation method of low-cost spherical Al-N-based powder
By using sucrose and γ-aluminum dioxide and other materials for wet grinding, spray granules and sintering, prepare a low-cost spherical Al-N base powder with adjustable thermal conductivity, solving the spherical Al2O3 and spherical Aln in the existing technology The lack of powder has achieved efficient heat dissipation performance and low -cost production.
Patent Information
- Application Number
- CN202411948633.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, spherical Al2O3 is difficult to meet the heat dissipation needs under high frequency, high speed, and high heat flow density conditions, and the preparation cost of spherical AlN powder is high, which limits the development of the integrated circuit industry.
Use sucrose as a carbon source, γ-aluminum, calcium fluoride, and aluminum nitride crystal species for wet grinding, spray granules and sintering. By controlling the heat insulation time during sintering, the adjustment coefficient can be adjusted.
The prepared low-cost spherical AL-N base powder has a high thermal conductivity, low cost, and avoiding uneven heat dissipation, which is suitable for high-performance integrated circuit industry.
Smart Images

Figure CN119371212A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic powders, and in particular to a low-cost spherical Al-N-based powder with adjustable thermal conductivity and a preparation method thereof. Background Art
[0002] Integrated circuit technology, as the core of information technology, is not only the cornerstone of economic development, but also related to national security and strategic competitive position. With the miniaturization, high integration and high performance of chips, electronic packaging technology has higher and higher requirements for the thermal conductivity of thermal interface materials, and heat dissipation has become an important bottleneck problem restricting the development of electronic technology. The new generation of thermal management materials and technologies for high-frequency, high-speed and high heat flux density working conditions of chips is a key link that needs to be broken through in the integrated circuit industry chain. Due to the advantages of high insulation and high processability of organic / inorganic composite materials, they are widely used in the field of thermal interface materials. Among them, inorganic fillers with high thermal conductivity are the key to determining the thermal conductivity of organic / inorganic composite materials. Spherical Al2O3 has the advantages of high thermal conductivity, high resistivity, low dielectric loss and high cost performance. It is the most used thermal conductive filler on the market. The thermal conductivity of the thermal interface material prepared by it is concentrated in 2-5W / m·K.
[0003] However, the intrinsic thermal conductivity of Al2O3 is only 38-42W / m·K. With the rapid development of integrated circuit technology, the requirements for heat dissipation are becoming more and more stringent. Spherical Al2O3 is difficult to meet future market demand. Therefore, it is imperative to develop new thermal conductive fillers with high thermal conductivity and high cost performance. Aluminum nitride (AlN) has extremely high thermal conductivity (320W / m·K), high resistivity (>1014), low expansion coefficient (4.7×10 -6 / K), low dielectric constant (8.8at1MHz), and high fluidity of spherical AlN, which fully meets the use requirements of the microelectronics industry, and the use of spherical AlN-based powders to replace the currently widely used spherical Al2O3 has become an inevitable trend. However, the current high-end electronic thermal conductivity field uses spherical AlN powders at a high price, and the high preparation cost of spherical AlN powders, which seriously restricts the development of the integrated circuit industry. It is urgent to develop spherical Al-N-based powders with independent intellectual property rights.
[0004] In addition, the current domestic solution for integrated circuits such as chips under high-frequency, high-speed, and high-heat flux density working conditions is usually to compound spherical alumina with spherical AlN to prepare high thermal conductivity composite powders. However, due to the problem of uneven mixing of spherical alumina and spherical AlN, the prepared high thermal conductivity composite powders have the problem of uneven heat dissipation. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a low-cost spherical Al-N-based powder with adjustable thermal conductivity and a preparation method thereof, which can reduce the preparation cost of the spherical Al-N-based powder, and the prepared spherical Al-N-based powder has high thermal conductivity and does not have the problem of uneven heat dissipation.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity, comprising: granulation, sintering; The granulation comprises adding aluminum oxide, sugar carbon, calcium fluoride and aluminum nitride seed crystals into a ball mill for wet grinding, and then drying to obtain a mixed raw material, and spray granulating the mixed raw material to obtain raw material particles; The alumina is γ-alumina with a mass purity of 99.5% and a particle size of 0.5-5 μm; The sugar carbon is sucrose; The molar ratio of sugar carbon to alumina is not less than 3.5:1; Preferably, the molar ratio of sugar carbon to alumina is 3.5-5:1; The calcium fluoride accounts for 1-10% of the total mass of aluminum oxide and sugar carbon; The aluminum nitride seed crystals account for 0-20% of the mass of aluminum oxide; The particle size of the aluminum nitride seed crystal is 0.8-1.2 μm; The mass ratio of ball material to water during wet grinding is 3-5:7:3.5-4.5, the rotation speed is 200-300rpm, and the wet grinding time is 12h; The drying temperature is 100-120°C and the drying time is 10-12h; The average particle size of the raw material particles is 50-52 μm; The sintering comprises placing the raw material particles into a sintering furnace for sintering to obtain sintered particles, and then placing the sintered particles into a muffle furnace for decarbonization to obtain low-cost spherical Al-N-based powders; The sintering is carried out in a nitrogen atmosphere, heating the temperature to 1750-1800° C. at a heating rate of 10-30° C. / min, and keeping the temperature at 1750-1800° C. for 4-10 hours; The decarbonization is carried out in an air atmosphere at a temperature of 700-800° C. for 7-8 hours.
[0007] A low-cost spherical Al-N-based powder with controllable thermal conductivity obtained by the above-mentioned preparation method.
[0008] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity of the present invention uses sucrose as a carbon source and alumina as an aluminum source. By controlling the holding time during sintering, the thermal conductivity is adjustable, thereby promoting the upgrading and replacement of low-cost ceramic thermal conductive fillers used in the field of thermal interfaces and the improvement of engineering application technology, providing key materials and technical support for the development of my country's high-performance integrated circuit industry. It is very suitable as a high thermal conductivity inorganic filler and can significantly improve the thermal conductivity of polymer composite materials, making it more widely used in the fields of aerospace, electronics, and chemical industry. (2) The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity of the present invention has lower preparation cost than spherical AlN powder; (3) The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity of the present invention, wherein the thermal conductivity of the prepared low-cost spherical Al-N-based powder is 97.1-196.2 W / m•K and the bulk density is 1.1-1.7 g / cm 3 The oil absorption value is 27-37%, the sphericity is 96.8-98.2%, the carbon mass content is 0.1-0.8%, the D50 particle size is 21-32μm, and the hydrolysis resistance time in a water bath at 85℃ is 74-82h. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is a scanning electron microscope image of the raw material particles obtained in Example 1, with a magnification of 100 times; Figure 2 This is a scanning electron microscope image of the raw material particles obtained in Example 1, with a magnification of 250 times; Figure 3 This is a scanning electron microscope image of the low-cost spherical Al-N-based powder obtained in Example 1, with a magnification of 250 times; Figure 4 This is a scanning electron microscope image of the low-cost spherical Al-N-based powder obtained in Example 1, with a magnification of 2300 times; Figure 5 This is a schematic diagram of the preparation principle of low-cost spherical Al-N based powder in Example 1. DETAILED DESCRIPTION
[0010] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0011] Example 1 A method for preparing low-cost spherical Al-N-based powder, specifically: 1. Alumina, sugar carbon and calcium fluoride were added to a ball mill and wet-milled for 12 hours, the mass ratio of ball material to water during ball milling was controlled to be 3:7:3.5, the rotation speed was 200 rpm, and then dried, the temperature during drying was controlled to be 100°C, the time was 12 hours, and a mixed raw material was obtained. The mixed raw material was spray granulated to obtain raw material particles with an average particle size of 50 μm. The obtained raw material particles were subjected to scanning electron microscopy analysis, and the obtained scanning electron microscopy image is shown in Figure 1 and Figure 2 ; The alumina is γ-alumina with a mass purity of 99.5% and a particle size of 5 μm; The sugar carbon is sucrose; The molar ratio of sugar carbon to alumina is 5:1; The calcium fluoride accounts for 10% of the total mass of aluminum oxide and sugar carbon; The aluminum nitride seed crystals account for 20% of the mass of aluminum oxide; The particle size of the aluminum nitride seed crystal is 1 μm; 2. The raw material particles are placed in a sintering furnace for sintering, specifically, in a nitrogen atmosphere, the temperature is raised to 1750°C at a heating rate of 10°C / min, and the temperature is kept at 1750°C for 4 hours to obtain sintered particles, and then the sintered particles are placed in a muffle furnace for decarbonization in an air atmosphere, and the temperature during decarbonization is controlled to be 700°C and the time is 8 hours to obtain low-cost spherical Al-N-based powder; The low-cost spherical Al-N-based powder has a thermal conductivity of 97.1 W / m•K and a bulk density of 1.4 g / cm 3 , oil absorption value is 27%, sphericity is 98.2%, carbon mass content is 0.8%, D50 particle size is 26μm, hydrolysis resistance time in 85℃ water bath is 82h; The low-cost spherical Al-N-based powder obtained in this example was analyzed by scanning electron microscopy, and the obtained scanning electron microscopy image is shown in FIG. Figure 3 and Figure 4 ,Will Figure 2 and Figure 3 After comparison, it can be seen that after sintering in the sintering furnace, the particle size becomes smaller. Figure 4 It can be seen that the sintered particles obtained in this embodiment have achieved surface densification.
[0012] This embodiment also provides a low-cost spherical Al-N-based powder obtained by the aforementioned preparation method.
[0013] Example 2 A method for preparing low-cost spherical Al-N-based powder, specifically: 1. Add alumina, sugar carbon, calcium fluoride and aluminum nitride seeds into a ball mill and wet grind for 12 hours, control the mass ratio of ball material to water during ball milling to be 5:7:4.5, and the rotation speed to be 300 rpm, and then dry the mixture at a temperature of 120°C for 10 hours to obtain a mixed raw material, and spray granulate the mixed raw material to obtain raw material particles with an average particle size of 52 μm; The alumina is γ-alumina with a mass purity of 99.5% and a particle size of 0.5 μm; The sugar carbon is sucrose; The molar ratio of sugar carbon to alumina is 3.5:1; The calcium fluoride accounts for 1% of the total mass of aluminum oxide and sugar carbon; The aluminum nitride seed crystals account for 20% of the mass of aluminum oxide; 2. The raw material particles are placed in a sintering furnace for sintering, specifically, in a nitrogen atmosphere, the temperature is raised to 1800°C at a heating rate of 30°C / min, and the temperature is kept at 1800°C for 4 hours to obtain sintered particles, and then the sintered particles are placed in a muffle furnace and decarbonized in an air atmosphere, and the temperature during decarbonization is controlled to be 800°C and the time is 7 hours to obtain low-cost spherical Al-N-based powder; The low-cost spherical Al-N-based powder has a thermal conductivity of 103.8 W / m•K and a bulk density of 1.1 g / cm 3 The oil absorption value is 34%, the sphericity is 98.2%, the carbon mass content is 0.8%, the D50 particle size is 32μm, and the hydrolysis resistance time in a water bath at 85℃ is 78h.
[0014] This embodiment also provides a low-cost spherical Al-N-based powder obtained by the aforementioned preparation method.
[0015] Example 3 On the basis of Example 1, the holding time at 1750°C in step 2 was extended from 4 h to 5 h, and the thermal conductivity of the obtained low-cost spherical Al-N-based powder was 112.5 W / m•K and the bulk density was 1.5 g / cm 3 The oil absorption value is 30%, the sphericity is 98%, the carbon mass content is 0.7%, the D50 particle size is 25μm, and the hydrolysis resistance time in a water bath at 85℃ is 80h.
[0016] Example 4 On the basis of Example 1, the holding time at 1750°C in step 2 was extended from 4 h to 6 h, and the thermal conductivity of the obtained low-cost spherical Al-N-based powder was 129.0 W / m•K and the bulk density was 1.5 g / cm 3The oil absorption value is 31%, the sphericity rate is 98.1%, the carbon mass content is 0.7%, the D50 particle size is 24μm, and the hydrolysis resistance time in a water bath of 85℃ is 79h.
[0017] Example 5 On the basis of Example 1, the holding time at 1750°C in step 2 was extended from 4 h to 7 h, and the thermal conductivity of the obtained low-cost spherical Al-N-based powder was 148.7 W / m•K and the bulk density was 1.6 g / cm 3 The oil absorption value is 33%, the sphericity is 97.4%, the carbon mass content is 0.4%, the D50 particle size is 23μm, and the hydrolysis resistance time in a water bath at 85℃ is 78h.
[0018] Example 6 On the basis of Example 1, the holding time at 1750°C in step 2 was extended from 4 h to 8 h, and the thermal conductivity of the obtained low-cost spherical Al-N-based powder was 171.0 W / m•K and the bulk density was 1.7 g / cm 3 The oil absorption value is 34%, the sphericity is 97.3%, the carbon mass content is 0.3%, the D50 particle size is 22μm, and the hydrolysis resistance time in a water bath at 85℃ is 77h.
[0019] Example 7 On the basis of Example 1, the holding time at 1750°C in step 2 was extended from 4 h to 9 h, and the thermal conductivity of the obtained low-cost spherical Al-N-based powder was 195.7 W / m•K and the bulk density was 1.7 g / cm 3 The oil absorption value is 37%, the sphericity is 96.8%, the carbon mass content is 0.2%, the D50 particle size is 22μm, and the hydrolysis resistance time in a water bath at 85℃ is 74h.
[0020] Example 8 On the basis of Example 1, the holding time at 1750°C in step 2 was extended from 4 h to 10 h, and the thermal conductivity of the obtained low-cost spherical Al-N-based powder was 196.2 W / m•K and the bulk density was 1.7 g / cm 3 The oil absorption value is 37%, the sphericity is 97.1%, the carbon mass content is 0.1%, the D50 particle size is 21μm, and the hydrolysis resistance time in a water bath at 85℃ is 74h.
[0021] It can be seen from the thermal conductivity of the low-cost spherical Al-N-based powder prepared in Examples 1 and 3-8 that with the extension of the holding time at 1750°C, the thermal conductivity gradually increases, indicating that with the extension of the holding time, the mass content of aluminum nitride in the prepared low-cost spherical Al-N-based powder gradually increases.
[0022] The preparation principle diagram of low-cost spherical Al-N based powder in Example 1 is shown in Figure 5 As shown by Figure 5 It can be seen that in the process of ball milling, spray granulation, sintering and carbon removal after mixing with alumina, calcium fluoride and the like, calcium fluoride is used as a sintering aid, and sucrose can be used as a carbon source on the one hand, and can also act as a binder on the other hand, thereby ensuring that particles can be obtained in the spray granulation without adding a binder, and then when sintering in the sintering furnace, the temperature is rapidly increased at a faster heating rate. In the process of rapid heating, after reaching a certain temperature, the sucrose can be rapidly carbonized and expanded, thereby increasing the particle size of the prepared single particle. After the sintering is completed, large-size particles containing carbon are obtained. The large-size particles The main components are aluminum oxide and aluminum nitride, and then decarbonization is carried out in a muffle furnace to remove the carbon in the large-size particles. At the same time, the large-size particles shrink to obtain monodisperse particles. The components of the monodisperse particles are aluminum oxide and aluminum nitride. The content of aluminum nitride determines the thermal conductivity of the monodisperse particles. During sintering in a sintering furnace, there are two reactions: carbon thermal reduction of aluminum oxide to generate aluminum and aluminum reacting with nitrogen to generate aluminum nitride. Among them, the reaction rate of carbon thermal reduction of aluminum oxide to generate aluminum is slow. Therefore, the speed of carbon thermal reduction of aluminum oxide to generate aluminum can be controlled by adjusting the sintering time, thereby controlling the amount of aluminum nitride generated, and further realizing adjustable thermal conductivity. In addition, it is also possible to combine aluminum oxide and aluminum nitride into monodisperse particles through the bonding effect of sucrose and the rapid carbonization and expansion effect at high temperature, thereby avoiding the problem of uneven heat dissipation caused by uneven mixing when aluminum oxide and aluminum nitride are directly mixed in the prior art.
[0023] Unless otherwise specified, all percentages used in the present invention are by mass.
[0024] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a low-cost spherical Al-N-based powder with adjustable thermal conductivity, characterized in that: include: Granulation, sintering; The granulation comprises adding aluminum oxide, sugar carbon, calcium fluoride and aluminum nitride seed crystals into a ball mill for wet grinding, and then drying to obtain a mixed raw material, and spray granulating the mixed raw material to obtain raw material particles; The sintering process includes placing the raw material particles into a sintering furnace for sintering to obtain sintered particles, and then placing the sintered particles into a muffle furnace for decarbonization to obtain low-cost spherical Al-N-based powder.
2. The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity according to claim 1, characterized in that: The alumina is γ-alumina with a mass purity of 99.5% and a particle size of 0.5-5 μm.
3. The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity according to claim 1, characterized in that: The sugar carbon is sucrose; The molar ratio of the sugar carbon to alumina is not less than 3.5:
1.
4. The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity according to claim 1, characterized in that: The calcium fluoride accounts for 1-10% of the total mass of the aluminum oxide and the sugar carbon.
5. The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity according to claim 1, characterized in that: The aluminum nitride seed crystals account for 0-20% of the mass of aluminum oxide; The particle size of the aluminum nitride seed crystal is 0.8-1.2 μm.
6. The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity according to claim 1, characterized in that: The mass ratio of ball material to water in the wet grinding is 3-5:7:3.5-4.5, the rotation speed is 200-300rpm, and the wet grinding time is 12h; The temperature during the drying is 100-120° C. and the time is 10-12 hours.
7. The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity according to claim 1, characterized in that: The average particle size of the raw material particles is 50-52 μm.
8. The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity according to claim 1, characterized in that: The sintering is carried out in a nitrogen atmosphere, heating the temperature to 1750-1800° C. at a heating rate of 10-30° C. / min, and keeping the temperature at 1750-1800° C. for 4-10 hours.
9. The method for preparing low-cost spherical Al-N-based powder with adjustable thermal conductivity according to claim 1, characterized in that: The decarbonization is carried out in an air atmosphere at a temperature of 700-800° C. for 7-8 hours.
10. A low-cost spherical Al-N-based powder with controllable thermal conductivity obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of aluminum nitride powder
CN109879257A
Preparation method of aluminum nitride based on organic carbon source
CN116443824A
Micron-sized spherical aluminum nitride powder, preparation method and application
CN116891225A
Preparation method of aluminum nitride powder
CN117447209A
Process for producing aluminum nitride and a special aluminum nitride itself
WO2018134259A1